Sistema telemático para el control y monitoreo de invernaderos de la Universidad Técnica Estatal de Quevedo campus “La María” - Casquete Menéndez, Shirley Stefania (2023)
This project focuses on enhancing agricultural management in greenhouses through the application of advanced technologies. The general objective is to develop a telematic system using low-power networks and a suitable framework to optimize the management of the greenhouses at the 'La María' Campus of the Technical State University of Quevedo. To achieve this, specific objectives are set, including the identification of requirements for monitoring and controlling environmental variables, the implementation of a telematic network infrastructure, and the development of an intuitive user interface. Sensors and IoT technology will be used to collect environmental data and enable real-time data-driven decision-making.